Case report: A rare case of renal tuberculosis combined with bladder cancer - Xiang, Yang; Wen, Zhou; Yang, Meng; Lyu, Han; Chen, Zongyu; Yuan, Dongbo; Zhu, Jianguo (Frontiers in Oncology, 2024)
We report a case of renal tuberculosis combined with bladder cancer. The patient was a 57-year-old man with no history of tuberculosis who presented with hematuria and signs of urinary tract irritation. Computed tomography (CT) showed florid, bowel-filling calcifications at the level of the right renal hilum, multiple hyperdense shadows from the right renal pelvis to the ureter, and left pyelo-ureteral effusion. Enhanced CT showed localized protrusion and marked enhancement of bladder tissue. Blood TSPOT.TB was positive, erythrocyte sedimentation rate (ESR) was increased, and urine Mycobacterium tuberculosis DNA was negative. Cystoscopy showed an irregular bulge at the bladder neck opening, and pathological examination diagnosed high-grade papillary carcinoma of the uroepithelium. The diagnosis was tuberculosis of the right kidney and bladder tumor. The patient was re-visited due to anuria for 2 days and underwent emergency left percutaneous nephrostomy (PCN) to improve the left kidney function. Given the potential for extensive infiltration into the muscular layer of the bladder tumor, a transurethral resection of the bladder tumor (TURBT) was advocated as an initial step to obtain tissue for diagnostic confirmation. Following this, a right nephrectomy and radical cystectomy to address the bladder cancer would have been performed. Nevertheless, the patient declined surgery due to the associated risks and succumbed to the illness 7 months post-follow-up. This is a rare case, and informed consent was obtained from the patient and her family.